Applications of vegetable oils and their derivatives as Bio-Additives for use in asphalt binders: A review. (20th June 2023) - Chen, Conglin; Lu, Jinbo; Ma, Tao; Zhang, Yang; Gu, Linhao; Chen, Xiang
Graphical abstract: Highlights: The properties of vegetable oils and their applications in asphalt are summarized. Functionalized vegetable oils have better modification or regeneration effects. Functionalized vegetable oils may interact with asphalt physically and chemically. Biopolymers can replace traditional counterparts in asphalt modification. Vegetable oil-based additives are used as rejuvenators, fluxing agents or modifiers. Abstract: Vegetable oils and their derivatives have shown great potential as modifiers or rejuvenators for use in asphalt materials with promising performance. Due to the environmental and economic benefits, investigations on using vegetable oils in an effective way to enhance performance and promote interaction with asphalt materials have been further conducted in recent decades. This paper reviews the state of the art on the applications of vegetable oils and their derivatives as bio-additives for use in asphalt binders, which includes the use of plant based-oil (vegetable oil and waste vegetable oil), functionalized vegetable oil (epoxidized, transesterified, and acrylated vegetable oils), and vegetable oil-based polymer (soybean oil-based and castor oil-based biopolymer). Emphasis is given on the continuous optimization of vegetable oil's chemical structure to improve its compatibility and interaction with asphalt. The advantages and disadvantages of using various vegetable oils and their derivatives in asphalt modification in terms of blending protocol, interaction mechanism, and performance are summarized and highlighted. This paper attempts to provide valuable guidance for the options of vegetable oil-based materials regarding the target performance of modified asphalt and may provide insights towards the design of new vegetable oil-based materials for use in asphalt.